Laccase: An Environmental Benign Pretreatment Agent for Efficient Bioconversion of Lignocellulosic Residues to Bioethanol - Nawaz, Ali; Mukhtar, Hamid; ul Haq, Ikram; Mazhar, Zainab; Mumtaz, Muhammad W. (Current Organic Chemistry, 2019)
Abrupt urbanization and industrialization around the world resulted in elevated environmental pollution and depletion of natural energy resources. An eco-friendly and economical alternative for energy production is the need of an hour. This can be achieved by converting the waste material into energy. One such waste is lignocellulosic agricultural residues, produced in billions of tons every year all around the world, which can be converted into bioethanol. The main challenge in this bioconversion is the recalcitrant nature of lignocellulosic material. The removal of cementing material is lignin and to overcome the potential inhibitors produced during the disintegration of lignin is the challenging task for biotechnologist. This task can be achieved by a number of different methods but laccase is the most effective and eco-friendly method that can be used for effective removal of lignin along with the increase the accessibility of cellulose and bioethanol yield.
Keywords: urbanization